Behavior profile and life habits of men in the face of masculinity - Daiana Jesus da Hora, Suzicléia Elizabete de Jesus Franco, Marcos Vinicius Costa Santos, Fernando Riegel, Alisséia Guimarães Lemes, Elias Marcelino Rocha (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v9i0.9202